2008
DOI: 10.20882/adicciones.264
|View full text |Cite
|
Sign up to set email alerts
|

¿Es bueno el alcohol para la salud?

Abstract: Algunos estudios observacionales de seguimiento sobre salud cardiovascular han encontrado una coincidencia entre el consumo moderado de alcohol y una menor mortalidad prematura, debida a un infarto de miocardio o a otras causas. Dichos estudios cuentan con importantes limitaciones metodológicas. La mayoría de personas que pertenecían al grupo de abstemios, en realidad eran ex-bebedores, es decir, personas que habían tenido que dejar de beber alcohol debido a que sufrían alguna enfermedad. Además, no se han eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…A large body of evidence supports the mediating role of opioid receptors on ethanol intake, and the antagonism of this system is a common therapeutic target on AUD treatment. 24,25,29 Recent studies have reported a similar role of opioid receptors antagonism on BE as well. 30 Furthermore, both ethanol intake and BE have been reduced by modulating other pharmacological targets such as corticotropin-releasing factor, 31,32 dopamine receptors 33,34 and sigma-1 receptor, 35,36 which support the connection between the two behaviours.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A large body of evidence supports the mediating role of opioid receptors on ethanol intake, and the antagonism of this system is a common therapeutic target on AUD treatment. 24,25,29 Recent studies have reported a similar role of opioid receptors antagonism on BE as well. 30 Furthermore, both ethanol intake and BE have been reduced by modulating other pharmacological targets such as corticotropin-releasing factor, 31,32 dopamine receptors 33,34 and sigma-1 receptor, 35,36 which support the connection between the two behaviours.…”
Section: Discussionmentioning
confidence: 85%
“…The significant decrease of the ethanol consumption observed after the administration of naltrexone (10 mg/kg) supports this hypothesis and is congruent with previous research. 25 However, future studies should include additional combinations of ethanol concentrations and eating conditions, to assess interactions with systems other than the opioid system. This novel model of ethanol consumption induced by a BE experience implies a new approach, sharply different from other ethanol self-administration methods, such as operant models that require lever pressing, or chronic or episodic access, or the drinking in the dark procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation